Transcriptomic and Genetic Analyses Identify the Krüppel-Like Factor Dar1 as a New Regulator of Tube-Shaped Long Tendon Development - Laurichesse, Quentin; Moucaud, Blandine; Laddada, Lilia; Renaud, Yoan; Jagla, Krzysztof; Soler, Cédric (Frontiers in Cell and Developmental Biology, 2021)
To ensure locomotion and body stability, the active role of muscle contractions relies on a stereotyped muscle pattern set in place during development. This muscle patterning requires a precise assembly of the muscle fibers with the skeleton via a specialized connective tissue, the tendon. Like in vertebrate limbs, Drosophila leg muscles make connections with specific long tendons that extend through different segments. During the leg disc development, cell precursors of long tendons rearrange and collectively migrate to form a tube-shaped structure. A specific developmental program underlies this unique feature of tendon-like cells in the Drosophila model. We provide for the first time a transcriptomic profile of leg tendon precursors through fluorescence-based cell sorting. From promising candidates, we identified the Krüppel-like factor Dar1 as a critical actor of leg tendon development. Specifically expressed in the leg tendon precursors, loss of dar1 disrupts actin-rich filopodia formation and tendon elongation. Our findings show that Dar1 acts downstream of Stripe and is required to set up the correct number of tendon progenitors.